PELATIHAN PENENTUAN DOSIS PUPUK OKGANIK SPESIFIK LOKASI PADA TANAMAN HORTIKULTURA DI KELOMPOK TANI MOAWOTA DESA BULOTALANGI KABUPATEN BONE BOLANGO - Nurdin, Nurdin,; Rahman, Rival; Adam, Echan; Apriliani, Silvana; Bahi, Iin Veronika (Universitas Negeri Gorontalo, 2025)
The potential for using organic fertilizer as a substitute for inorganic fertilizer is enormous, but many farmers still do not know how to determine site-specific organic fertilizer dosages for horticultural crops. This activity aims to increase farmers' knowledge about determining site-specific organic fertilizer dosages for horticultural crops in the Moawota Farmers Group, Bulotalangi Village, Bone Bolango Regency. The training method used in this activity was with 20 participants who were evaluated before and after the training for their knowledge improvement achievements. The results obtained showed that the training on determining organic fertilizer dosages in general has been able to increase farmers' knowledge by 93% from only 29% before the training. To make the results of this training more effective, it is recommended that intensive mentoring be provided to farmers by both agricultural extension workers and academics until the application of organic fertilizer dosages on horticultural crops and evaluation of their agronomic performance and economic aspects.